PENYELESAIAN SENGKETA EKONOMI SYARIAH MELALUI BASYARNAS DITINJAU DARI ASAS KEPASTIAN HUKUM, KEADILAN DAN KEMANFAATAN - Syams Eliaz Bahri (IAIN Batusangkar, 2017)
This research was aimed at analyzing the resolution dispute of sharia economic through BASYARNAS in terms of legal certainly, justice, and benefits. BASYARNAS was born as a response to the development of sharia financial institutions. The verdict issued by the arbitration body (BASYARNAS) is final and binding. In this case whether the dispute settlement through BASYARNAS has reflected the value of legal certainty, justice and expediency. This research is qualitative with normative juridical approach, data obtained from literature study and analyzed qualitatively. The results of this research seen the overlapping law that resulted in confusion on the execution of the decision BASYARNAS. The overlapping law esulted in the non-creation of legal certainty and made it difficult for justice seekers.